Phase-Transfer and Ion-Pairing Catalysis of Pentanidiums and Bisguanidiniums - Zong, Lili (2018)
Catalysts accelerate biological processes and organic reactions in a controlled and selective fashion. There are continuing efforts in asymmetric catalysis to develop efficient catalysts with broad reaction scope and industrial practicability. Among the various modes of asymmetric catalysis, phase-transfer catalysis has attracted intense interest due to its facile scale up and low catalyst loading. Chiral quaternary ammonium and phosphonium salts are well-studied classes of chiral phase-transfer catalysts, and they are typically composed of sp3-hybridized quaternary onium salts. In this Account, we describe our recent attempts to develop N-sp2-hybridized guanidinium-type salts as efficient phase-transfer catalysts as well as ion-pair catalysis based on N-sp2 hybridized bisguanidinium-type salts.